2003
DOI: 10.1021/np030193e
|View full text |Cite
|
Sign up to set email alerts
|

The Macrocidins:  Novel Cyclic Tetramic Acids with Herbicidal Activity Produced by Phoma macrostoma

Abstract: Field isolates of Phoma macrostoma were obtained from diseased Canada thistle growing in several geographically diverse regions. Bleaching and chlorotic symptoms were present on the infected plants. The isolates grown in liquid culture were found to produce phytotoxic metabolites which also caused bleaching when applied foliarly to several broadleaf species. Bioassay-directed isolation led to the discovery of macrocidins A and B, the first representatives of a new family of cyclic tetramic acids. This new chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 18 publications
5
85
0
Order By: Relevance
“…The 1 H NMR spectrum of the pigment revealed the presence of seven aromatic protons, four of which showed a doublet at G 6.91, 6.85, 6.66, and 6.94 ppm, whereas the remaining three showed a sharp aromatic proton singlet at G 7.26, 7.10, and 7.25 ppm. Comparison of these data with those reported in the literature revealed that the new anthraquinone corresponds to a combination of subunits -A (torosachrysone-8-O-methylether) and B (emodin-1-O-methyl ether) joined at the C-10c and C-5 position, respectively [6][7][8]. The structure of the compound was further confirmed by the 13 C NMR data, which show a total of 30 carbon resonances.…”
supporting
confidence: 70%
“…The 1 H NMR spectrum of the pigment revealed the presence of seven aromatic protons, four of which showed a doublet at G 6.91, 6.85, 6.66, and 6.94 ppm, whereas the remaining three showed a sharp aromatic proton singlet at G 7.26, 7.10, and 7.25 ppm. Comparison of these data with those reported in the literature revealed that the new anthraquinone corresponds to a combination of subunits -A (torosachrysone-8-O-methylether) and B (emodin-1-O-methyl ether) joined at the C-10c and C-5 position, respectively [6][7][8]. The structure of the compound was further confirmed by the 13 C NMR data, which show a total of 30 carbon resonances.…”
supporting
confidence: 70%
“…The active metabolite eluted at a retention time of 6.9 min based on bioassay against Echinochloa crus-galli and Helianthus annuus using procedures described earlier. 12 …”
Section: Fermentation and Isolationmentioning
confidence: 99%
“…Phoma macrostoma (Montagne) is an effective bioherbicidal fungus against broadleaf weeds (Bailey and Derby, 2001) (Graupner et al, 2003). Monocots such as turfgrasses, wheat (Triticum aestivum L.) and barley (Hordeum vulgare L.), as well as some dicots, including pumpkin (Cucurbita L. spp), are resistant to P. macrostoma and macrocidins (Bailey et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the symptom similarity to known carotenoid biosynthesis inhibitors, it was hypothesised that macrocidins inhibit one of more steps in carotenoid production. However, it has been shown that macrocidins do not inhibit the enzyme hydroxyphenyl pyruvate dioxygenase (HPPD) (Graupner et al, 2003) which is required for the formation of plastoquinone, a co-factor needed for carotenoid biosynthesis (Norris et al, 1995).…”
Section: Introductionmentioning
confidence: 99%